Factors Predicting Intention to Quit Smoking among Psychiatric Patients with Depression - Saithanwanitkul, Montha; Suttharangsee, Wandee; Chanchong, Weena (Nursing Science Journal of Thailand, 2019)
Purpose: This research aimed to study predicting factors on intention to quit smoking among psychiatric patients with depression. Design: Correlational predictive study. Methods: The subjects were 132 psychiatric patients with depression who currently smoked. They were outpatients of psychiatric hospitals and mental health clinics in general hospitals in the south of Thailand who met inclusion criteria. The research instrument consisted of 7 parts: 1) general information questionnaire, 2) cigarette information questionnaire, 3) Fagerstrom test for nicotine dependence, 4) intention to quit smoking in psychiatric patient with depression questionnaire, 5) attitude toward quit smoking in psychiatric patient with depression questionnaire, 6) subjective norm to quitting smoking in psychiatric patient with depression questionnaire, and 7) perceived behavioral control to quit smoking in psychiatric patient with depression questionnaire. Data were analyzed using descriptive statistics and multiple regression analysis. Main findings: The results showed that level of perceived behavioral control to quit smoking and nicotine dependence could explain 11% of intention to quit smoking in psychiatric patients with depression (R2 = .110, p = .010) The factors that significantly predicted intention to quit smoking in psychiatric patients with depression were perceived behavioral control to quit smoking (β = .283, t = 3.411, p = .001) and level of nicotine dependence (β = - .193, t = 2.334, p = .021). Conclusion and recommendations: The result showed the statistically significant prediction of perceived behavioral control to quit smoking and nicotine dependence on intention to quit smoking in psychiatric patient with depression. Therefore, nurse should develop a guideline for assessing smoking behavior. Furthermore, nurse should increase an intention to quit smoking by reinforcing perceived behavioral control to quit smoking together with nicotine replacement therapy for making an effective smoking cessation among psychiatric patient with depression.